(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The primary goal of the study is to determine the overall change in investors' investment preferences prior to and during the epidemic. This study is being performed to learn about investors' behavior before and during the epidemic. A descriptive research design is used to study the investment trend. A 200-person sample poll with a structured questionnaire was conducted to determine the impact of the pandemic on individual investment decisions. Primary and secondary data are collected in line with the needs of the research project. The study's primary data were acquired using a simple random sample method, while secondary data were obtained from government documents, websites, journal articles, theses, and books. I discovered that investors' investing choices alter, with a significant shift from mutual funds to fixed deposits due to market instability.